2015
DOI: 10.2967/jnumed.115.161117
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a Single-Time-Point Somatostatin Receptor SPECT/Multiphase CT Protocol in the Diagnostic Work-up of Gastroenteropancreatic Neuroendocrine Neoplasms

Abstract: This prospective study compared a 1-d SPECT/CT protocol with the commonly used 3-d protocol for somatostatin receptor scintigraphy in patients with gastroenteropancreatic neuroendocrine neoplasms. Additionally, the influence of SPECT/CT on patient management was evaluated. Methods: From October 2011 to October 2012, all gastroenteropancreatic neuroendocrine neoplasm patients undergoing restaging with somatostatin receptor scintigraphy on a modern SPECT/CT device were enrolled in this study. The protocol consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Consistent with previous reports, the age-adjusted annual incidence of fNENs has gradually risen over the past decade, in which Grade 1 and localized fNENs rose markedly [ 14 , 15 ]. This is possibly attributed to the detection of asymptomatic early-stage disease after the extensive use of endoscopy and computed tomography [ 20 ]. Notably, the morbidity of different sites presented obvious discriminations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous reports, the age-adjusted annual incidence of fNENs has gradually risen over the past decade, in which Grade 1 and localized fNENs rose markedly [ 14 , 15 ]. This is possibly attributed to the detection of asymptomatic early-stage disease after the extensive use of endoscopy and computed tomography [ 20 ]. Notably, the morbidity of different sites presented obvious discriminations.…”
Section: Discussionmentioning
confidence: 99%
“…Although fNENs of the lung, rectum and intestine occupy the majority, the appendiceal fNENs showed an unexpectedly tremendous increase (11-fold). Interestingly, the phenomenon was observed in recent years, partly attributed to a better understanding of the pathophysiologic presentation of NENs, improved classification system, as well as availability of advanced imaging modalities [20][21][22]. Another reason may be that pelvic surgery increased the probability of finding appendiceal fNEN [23].…”
Section: Discussionmentioning
confidence: 99%
“…Tc99m-HYNIC-Tyr3-Octreotide (Tektrotyd) has the advantage of ready availability of radio-isotope from departmental Technetium-99m generators, a single day imaging protocol and superior image resolution [7]. In addition the mean effective dose from Tc99m-Tektrotyd, reported to be 4.6 +/-1.1mSv [8], is significantly less than that for In-111-Octreotide at 8-16 mSv [9] Prior studies of In-111 SRS have shown that integration of SPECT/CT facilitates streamlining of imaging protocols with reduction in imaging time-points needed as it permits more reliable differentiation of pathological uptake from physiological activity [5,10]. Widely adopted In-111 SRS protocols recommend image acquisition at 24 (+/-48) hours' post-injection allowing 'wash-out' of accumulated bowel uptake of excreted tracer.…”
Section: Methodsmentioning
confidence: 99%
“…This study aimed to determine the feasibility of a streamlined imaging protocol in Tc99m-Tektrotyd SRS SPECT/CT with omission of 2-hour planar imaging, which, to the best of our knowledge has not been previously reported. Two prior studies have reported that use of SPECT/CT in In-111-labelled SRS allows rationalisation of dual time-point imaging to a single time-point protocol without impairment of diagnostic ability [5,10]. Our rationale for switching from In-111 SRS to Tc99m-Tektrotyd imaging of NETs included the superior image resolution afforded by the physical characteristics of Tc99m which make it better suited to gamma camera imaging, lower patient radiation exposure and increased availability of tracer from departmental generators permitting more flexibility in departmental workflow [7].…”
Section: Image Interpretationmentioning
confidence: 99%